2014
DOI: 10.3109/17453674.2014.961399
|View full text |Cite
|
Sign up to set email alerts
|

Single periarticular local infiltration analgesia reduces opiate consumption until 48 hours after total knee arthroplasty

Abstract: Background —Randomized trials evaluating efficacy of local infiltration analgesia (LIA) have been published but many of these lack standardized analgesics. There is a paucity of reports on the effects of LIA on functional capability and quality of life.Methods —56 patients undergoing unilateral total knee arthroplasty (TKA) were randomized into 2 groups in this placebo-controlled study with 12-month follow-up. In the LIA group, a mixture of levobupivacaine (150 mg), ketorolac (30 mg), and adrenaline (0.5 mg) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 16 publications
0
41
1
Order By: Relevance
“…A single LIA intraoperative injection seems to be the most effective treatment. 10,[20][21][22][23]33 Delayed infiltration during postoperative care doesn't seem to be more effective. 4,26,27 We decide to compare FNB associating LIA because previous studies had well indicated the effectiveness of these two methods in relieving pain after knee replacement surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A single LIA intraoperative injection seems to be the most effective treatment. 10,[20][21][22][23]33 Delayed infiltration during postoperative care doesn't seem to be more effective. 4,26,27 We decide to compare FNB associating LIA because previous studies had well indicated the effectiveness of these two methods in relieving pain after knee replacement surgery.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, LIA is limited in terms of its ability to provide long-lasting pain relief. 16,[31][32][33][34][35][36][37][38] The degree of knee flexion has been used to evaluate functional recovery following TKA. In the current study, active knee flexion ROM was significantly greater in the LIA group versus the PI group on POD1.…”
Section: Discussionmentioning
confidence: 99%
“…A trial that evaluated periarticular infiltration showed a 24% lower median cumulative consumption of oxycodone compared to controls at 48 hours [9]. Celecoxib reduced visual analog pain scores by 38% at 48 hours and reduced opioid requirements by 40% [10].…”
Section: Discussionmentioning
confidence: 99%